Assessment of shale gas potential of the lower Permian transitional Shanxi-Taiyuan shales in the southern North China Basin. Issue 2 (17th February 2021) - Li, P.; Zhang, J. C.; Tang, X.; Huo, Z. P.; Li, Z.; Luo, K. Y.; Li, Z. M.
Abstract: The geological research and exploration evaluation of marine–continental transitional shale gas are lagging behind the rapid development of marine and continental shale-gas resources in China. To investigate the shale-gas potential of the lower Permian Shanxi and Taiyuan formations in the southern North China Basin, a series of measurements on representative core samples were conducted to characterise shale features, including sedimentary environment, organic geochemistry, mineral composition, pore structure and gas-bearing capacity. The average total organic carbon (TOC) content of the Shanxi and Taiyuan shales reaches 1.68 and 2.26 wt%, respectively, and deposition took place in environments of rapidly changing depositional conditions, where predominantly gas-generating type III kerogen was preserved in the sediments. Regarding the sedimentary environments, different microfacies can affect effective thickness, abundance of organic matter, mineral composition and gas content in the Shanxi and Taiyuan formations. In addition, TOC content, inertinite, chlorite, thermal maturity and pyrite have significant impacts on gas contents. Although the Shanxi-Taiyuan shales are not comparable with gas-producing shales in the USA, there are some similarities in shale reservoir parameters such as the relatively higher organic richness (>2.0 wt% TOC) and gas content (∼2.0 m 3 /t) than in the well-developed Longmaxi and Yanchang shales. Consequently, the Shanxi-Taiyuan shales could be classified as potential shale-gas targets owing to their relatively favourable reservoir properties and gas accumulation. However, some complex geological conditions, such as the greater burial depth (>3500 m), higher clay content (>45%), deficiency of organic-matter hosted pores but other well-developed types of pore-microfracture, extremely high thermal maturity (>3.0% R o ), several large unsealed faults, etc . may impact gas production in the study areas. Therefore, local geological conditions should be fully considered for the exploration and development of transitional shale gas in the southern North China Basin. KEY POINTS: Main controlling factors of shale-gas content in transitional Shanxi-Taiyuan shales. Influence of sedimentary microfacies on shale reservoir parameters. Detailed investigation of transitional shale-gas potential in southern North China Basin, China.